Utilização de macrófitas aquáticas flutuantes no tratamento de efluentes de carcinicultura - Henares, Matheus Nicolino Peixoto [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Esta dissertação de mestrado está organizada em três capítulos. O capítulo I apresenta uma introdução geral, onde são abordados os impactos ambientais provocados pela atividade da aqüicultura e o tratamento de efluente por wetlands construídas. O capítulo II e III são referentes à experimentos desenvolvidos no Setor de Carcinicultura do Centro de Aqüicultura da UNESP (CAUNESP), em Jaboticabal – SP. Os principais objetivos destes capítulos foram: (Capítulo II) determinar os possíveis impactos provocados pelo manejo utilizado para a manutenção de camarões reprodutores da espécie Macrobrachium rosenbergii na água utilizada no viveiro; (Capítulo III) avaliar a eficiência de uma wetland construída e povoada com duas espécies de macrófitas aquáticas flutuantes (Eichhornia crassipes e Salvinia molesta) com diferentes exigências nutricionais para otimizar o tratamento do efluente de viveiro de manutenção de reprodutores de M. rosenbergii. O resultado do Capítulo II permite concluir que o manejo realizado para a manutenção de camarões reprodutores da espécie Macrobrachium rosenbergii entre as biomassas de 403,18 e 547,90 g.m-2, durante o período de 50 dias, provoca o aumento dos valores de condutividade elétrica, pH, turbidez e MPS; das concentrações de NIT, NT, P-PO4, PD e PT e reduz a concentração de O2 dissolvido. No Capítulo III, concluiu-se que a wetland construída e povoada com S. molesta e com E. crassipes + S. molesta foram menos eficiente no tratamento do efluente de viveiro de manutenção de M. rosenbergii do que a wetland construída e povoada com E. crassipes.

The world production of Malaysia shrimp, Macrobrachium rosenbergii, presented considerable growth in the last decades. However, shrimp farming activity can provoke impacts in water used in the vivarium. The aim of this work was to determine the possible impacts provoked by the management accomplished for the maintenance of reproductive shrimp of the species M. rosenbergii in water used in the vivarium during the period 50 day. In the beginning of the experiment (03/14/2007) the vivarium, located in the CAUNESP, in Jaboticabal (SP-Brazil), with 193 m2 of surface and 1.1 m was full of 1.263 reproductive shrimp with medium weight of 61.61 ± 16.55 g.indivíduo-1. Weekly, it was determined value of temperature, pH, dissolved oxygen, electric conductivity, total alkalinity, turbidity, particulate material in suspension (PMS), total inorganic nitrogen (TIN), total nitrogen (TN), orthophosphate (P-PO4), dissolved phosphorus (DP) and total phosohorus (TP) of supply water and of the effluent of the vivarium. The values of electric conductivity and pH were significantly (p<0,05) higher in the effluent relation to the ones of the supply water. The 25 turbidity and PMS values were significantly higher in the effluent of the vivarium in seven weeks. Except for the dissolved oxygen and of TN, the TIN, P-PO4, DP and TP concentrations were significantly higher in the effluent when compared to the supplu water of vivarium in all the weeks evaluated. Among the forms of phosphorus, the biggest increases were observed for DP and and TP concentrations with 82.76 μg.L-1 and 174.75 μg.L-1, respectively. Among nitrogeneous forms, the biggest increase was observed for TIN with 81.32 μg.L-1. The management accomplished for the reproductive maintenance of M. rosenbergii during the period 50 days caused impact in water used in the vivarium... (Complete abstract, click electronic access below)
Keywords: Efluente - Qualidade; Aquicultura; Macrófitas aquáticas; Efluent; Water quality; Shrimp farm activity; Malasya shrimp; Crustacean; nutrient